Transformasi Pers Islam di Era Reformasi - Budi Irawanto (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2006)
The 1998 Reformasi movement has contributed to the blossoming of pers freedom in Indonesia. Consequently, there has been a rapid growth in the number of print media, including the